Digital Marketing Strategy in Digital Transformation towards Industry 5.0: A Sustainable Development Goals (SDGs) Perspective - Tusiadi, Herman; Elsie, Elsie; Fernando, Liko (Asian Journal of Management Analytics, 2025)
This study explores the role of digital marketing strategies in supporting Sustainable Development Goals (SDGs) 8 (Decent Work and Economic Growth) and 9 (Industry, Innovation, and Infrastructure) within the industry 5.0 framework. Using a qualitative approach with semi-structured interviews involving 10 informants from MSMEs, practitioners, policymakers, and academics, data were collected through interviews, digital observations, and documentation. Thematic analysis using NVivo revealed that digital marketing fosters job creation, technology adoption (AI, CRM, landing pages), and sustainable innovation, while challenges remain in digital literacy and technological access. The study proposes an integrative framework to guide inclusive and sustainable digital marketing strategies that align with Industry 5.0 and the SDGs.